Chemical Characteristics of the Karmanasha River Water and Its Appropriateness for Irrigational Usage - Acharya, Anueva; Sharma, Motee Lal; Bishwakarma, Kiran; Dahal, Pragati; Chaudhari, Satyam Kumar; Adhikari, Barsha; Neupane, Shristi; Pokhrel, Badri Nath; Pant, Ramesh Raj (Journal of Nepal Chemical Society, 2020)
Water is a prime natural resource and precious national asset and one of the chief constituents of the environment. The chemical characteristics play a key role in terms of ecological and economic perspectives in the river water. The characterization and evaluation of river water quality in the Karmanasha River is necessary due to its immense importance in the livelihood of the people in the core urban areas of Kathmandu valley, Nepal. In this study, the surface water samples were collected from 16 sites with a 0.5 km interval to characterize and evaluate the water quality mainly from the perspective of its irrigational usage. The assessment was carried out by applying electrical conductivity (EC), sodium percentage (Na%), sodium adsorption ratio (SAR), permeability index (PI), Kelly’s ratio (KR), magnesium adsorption ratio (MAR), cation ratio of soil structural stability (CROSS), Wilcox diagram and water quality index (WQI) including the general hydrochemistry. The general hydrochemistry of river water indicates slightly alkaline in nature with mean pH value 8.07, and the dominance order of major ions follows the pattern of Ca2+>Mg2+>Na+>K+ for cations, and HCO3->Cl->NO3- for anions. Furthermore, the results revealed that the water is safe for irrigation purposes based on EC, Na%, SAR, KR, MAR, CROSS, and Wilcox diagram. The results also specified that no severe degradation in water, however, the low DO, and high BOD and COD values than that of the standard value prescribed by Nepal Drinking Water Quality Standard, signify the anthropogenic signature in the river water. This study provides the baseline information about the WQI and suitability of irrigation water quality, and further in-depth studies are required at spatiotemporal levels to get in-depth insights about the ecological health of the river.